INTEGRASI NILAI-NILAI SPIRITUAL LOKAL DALAM PENGEMBANGAN SLOW TOURISM BERBASIS BUDAYA DI PROVINSI GORONTALO - Dananjaya, Ahmad Ghazy (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2026)
The global shift towards slow tourism demands destinations to offer authentic and meaningful experiences. Gorontalo Province holds immense potential for spiritual tourism, yet its management lacks optimal integration. This study aims to analyze the influence of integrating religious rituals and local tradition values on spiritual tourism attraction. Employing a sequential explanatory mixed-method design, a survey was conducted on 200 tourists and analyzed using multiple linear regression, complemented by in-depth interviews with customary leaders. Empirical results demonstrate that religious rituals and local traditions have a positive and significant effect on spiritual tourism attraction, both partially and simultaneously. These findings imply that integrating spiritual values is a core element to strengthen tourism branding, increase the length of stay, and ensure the sustainability of Gorontalo's cultural heritage amidst modernization